Nyai Khairiyah Hasyim's Contribution Regarding Gender Equality in The Field of Education as an Insight Into Local History - Dewi, Meydi Endah Puspita; Yuliati, Yuliati (Postgraduate Program Magister Pendidikan Agama Islam, 2024)
Studies related to the contribution of nyai in the field of education in Indonesia have not received much attention due to gender differences as a barrier. This is because their position as a nyai is often underestimated and considered weak, inversely proportional to the contribution of kiai who get a better view. Nyai's contribution can clearly be seen from the actions they took in fighting for gender equality for women through education, one of which was by establishing pesantren. The contribution of Nyai Khairiyah Hasyim in the field of education as one of the Indonesian ulama is important to know as an insight into local history so that it is not forgotten by the times, especially the people of Jombang. This research aims to discuss and find out more about Nyai Khairiyah Hasyim's contribution to gender equality in the field of education, especially for women so that the contributions she has made as a female scholar, one of which is by establishing a pesantren, can be used as an insight into local history for the people of Jombang. The research method used in this research is a qualitative method and literature study by collecting data, reading, recording, then processing the data as research material from various sources such as books, journals and other sources related to the problem under study. Based on the explanation above, it can be concluded that studies related to Nyai Khairiyah Hasyim's contribution to gender equality in the field of education can be used as an insight into local history for the community because of her contribution in fighting for gender equality for women to get an education like men. Nyai Khairiyah Hasyim's contribution also had an impact on education both in Jombang and Indonesia. In addition, it is also so that the community and the next generation in Jombang do not forget her contribution in the field of education.